Identification and Estimation of Stochastic Bargaining Models - Merlo, Antonio; Tang, Xun (Econometrica, 2012)
Stochastic sequential bargaining models (Merlo and Wilson (1995, 1998)) have found wide applications in different fields including political economy and macroeconomics due to their flexibility in explaining delays in reaching an agreement. This paper presents new results in nonparametric identification and estimation of such models under different data scenarios.